Secondary metabolites of Leucaena leucochephala. Their relationship with some climate elements, different expressions of digestibility and primary metabolites - Herrera, R.; Verdecia, D. M.; Ramírez, J. L.; García, M.; Cruz, Ana M. (Cuban Journal of Agricultural Science, 2017)
Pearson correlation coefficients were established among secondary metabolites of Leucaena leucocephala and some climatic factors (maximum, minimum and mean temperature, rainfall and number of rainy days), primary metabolites and digestibility (organic matter, dry matter, protein and NDF). The metabolites were A) secondary: total tannins, total phenols, total condensed tannins, free condensed tannins, alkaloids, saponins, triterpenes, steroids and flavonoids and B) primary: glucose, fructose, sucrose and N. Secondary metabolites were correlated with the maximum temperature and the highest coefficient (r = 0.78) was for steroids. Similar result was obtained for condensed tannins bound to the fiber, but with the minimum temperature (r = -0.90). The highest coefficient for the number of rainy days was presented in flavonoids (r = 0.99), while for total rainfall coefficient, it was for total phenols (r = -0.90). Correlation coefficients between the secondary metabolites and OMD ranged from -0.57 to -0.74. For the in vitro of dry matter digestibility, they ranged between -0.65 and -0.94 and for NDF between -0.91 and -0.98. For PBD, the values were the lowest (-0.39 and 0.55). Considering the phenolic compounds as independent variables and related to alkaloids, saponins, triterpenes, steroids and flavonoids, the highest coefficients (≥0.80) were recorded by total tannins, total phenols, total condensed tannins and condensed tannins bound to fiber. When the secondary metabolites were related to the primary metabolites (glucose, fructose, sucrose and N), coefficients were negative and varied between -0.41 and -0.98. It can be concluded that the elements of the climate influenced the studied metabolites. All digestibility expressions were negatively affected by the presence of the secondary metabolites. Phenolic compounds were positively correlated with flavonoids, alkaloids, saponins, triterpenes and steroids, while primary metabolites correlated negatively with secondary metabolites. It is recommended to consider the results of this study in Leucaena leucocephala to assess the effect of climate change on the secondary metabolites, counteract the negative effect of these compounds on ruminant feeding systems, conduct future research to establish its maximum allowable value in the diet and apply the simulation and mathematical modeling to predict the performance of these substances in this and other plants. Key words: antinutritional factors, digestibility, legumes, temperature, rain